A novel piperidine identified by stem cell-based screening attenuates pulmonary arterial hypertension by regulating BMP2 and PTGS2 levels. Issue 4 (5th April 2018) - Xing, Yanjiang; Zhao, Shuang; Wei, Qingxia; Gong, Shiqiang; Zhao, Xin; Zhou, Fang; AI-Lamki, Rafia; Ortmann, Daniel; Du, Mingxia; Pedersen, Roger; Shang, Guangdong; Si, Shuyi; et al.
Genetic defects in bone morphogenetic protein type II receptor (BMPRII) signalling and inflammation contribute to the pathogenesis of pulmonary arterial hypertension (PAH). The receptor is activated by bone morphogenetic protein (BMP) ligands, which also enhance BMPR2 transcription. A small-molecule BMP upregulator with selectivity on vascular endothelium would be a desirable therapeutic intervention for PAH. We assayed compounds identified in the screening of BMP2 upregulators for their ability to increase the expression of inhibitor of DNA binding 1 (Id1), using a dual reporter driven specifically in human embryonic stem cell-derived endothelial cells. These assays identified a novel piperidine, BMP upregulator 1 (BUR1), that increased endothelial Id1 expression with a half-maximal effective concentration of 0.098 μmol·L −1 . Microarray analyses and immunoblotting showed that BUR1 induced BMP2 and prostaglandin-endoperoxide synthase 2 (PTGS2) expression. BUR1 effectively rescued deficient angiogenesis in autologous BMPR2 +/R899X endothelial cells generated by CRISPR/Cas9 and patient cells. BUR1 prevented and reversed PAH in monocrotaline rats, and restored BMPRII downstream signalling and modulated the arachidonic acid pathway in the pulmonary arterial endothelium in the Sugen 5416/hypoxia PAH mouse model. In conclusion, using stem cell technology we have provided a novel small-molecule compound which regulates BMP2 and PTGS2 levels that might be useful for the treatment of PAH. Stem cell technology identified a novel small-molecule compound that regulates BMP2 and PTGS2 levels in PAH http://ow.ly/l8R630iqf1R